Contactless Assessment of Cerebral Autoregulation by Photoplethysmographic Imaging at Green Illumination - Lyubashina, Olga A.; Mamontov, Oleg V.; Volynsky, Maxim A.; Zaytsev, Valeriy V.; Kamshilin, Alexei A. (Frontiers in Neuroscience, 2019)
Accurate and practical assessment of the brain circulation is needed to adequately estimate the viability of cerebral blood flow regulatory mechanisms in various physiological conditions. The objective of our study was to examine feasibility of the contactless green-light imaging photoplethysmography (PPG) for assessing cerebral autoregulation by revealing the dynamic relationships between cortical microcirculation assessed by PPG and changes in systemic blood pressure caused by visceral and somatic peripheral stimuli. In anesthetized male Wistar rats, the PPG video images of the open parietal cortex (either with unimpaired or dissected dura mater), electrocardiogram, and systemic arterial blood pressure (ABP) in the femoral artery were continuously recorded before, during and after visceral (colorectal distension) or somatic (tail squeezing) stimulation. In the vast majority of experiments with intact and removed dura mater, both spontaneous and peripheral stimulation-evoked changes in ABP negatively correlated with the accompanying alterations in the amplitude of pulsatile PPG component (APC), i.e. an increase of ABP resulted in a decrease of APC and vice versa. The most pronounced ABP and APC alterations were induced by noxious stimuli. Visceral painful stimulation in all cases caused short-term hypotension with simultaneous increase in cortical APC, whereas somatic noxious stimuli in 8 of 21 trials produced hypertensive effect with decreased APC. Animals with pressure 50-70 mmHg possessed higher negative cerebrovascular response rate of ABP-APC gradients than rats with either lower or higher pressure. Severe hypotension reversed the negative ratio to positive one, which was especially evident under visceral pain stimulation. Amplitude of the pulsatile PPG component probably reflects the regulation of vascular tone of cerebral cortex in response to systemic blood pressure fluctuations. When combined with different kinds of peripheral stimuli, the technique is capable for evaluation of normal and elucidation of impaired cerebrovascular system reactivity to particular physiological events, for example pain. The reported contactless PPG monitoring of cortical circulatory dynamics during neurosurgical interventions in combination with recordings of changes in other physiological parameters, such as systemic blood pressure and ECG, has the appealing potential to monitor viability of the cortex vessels and determine the state of patient’s cerebrovascular autoregulation.